2016
DOI: 10.1007/s12031-016-0728-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Uncoupling Protein 2 (UCP2) Regulates Retinal Ganglion Cell Number and Survival

Abstract: In the brain, mitochondrial uncoupling protein 2 (UCP2) has emerged as a stress signal associated with neuronal survival. In the retina UCP2 is expressed primarily by retinal ganglion cells. Here we investigated the functional relevance of UCP2 in the mouse retina. Increased expression of UCP2 significantly reduced apoptosis during the critical developmental period resulting in elevated numbers of retinal ganglion cells in the adult. Elevated UCP2 levels also protected against excitotoxic cell death induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 60 publications
4
25
0
Order By: Relevance
“…Previous studies have shown that greater levels of Ucp2 expression are protective against various conditions that increase oxidative stress, including excitotoxicity and MPTP-induced parkinsonism (Diano et al, 2003;Andrews et al, 2005;Barnstable et al, 2016). We have found that UCP2 is highly expressed in the inner retina (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Previous studies have shown that greater levels of Ucp2 expression are protective against various conditions that increase oxidative stress, including excitotoxicity and MPTP-induced parkinsonism (Diano et al, 2003;Andrews et al, 2005;Barnstable et al, 2016). We have found that UCP2 is highly expressed in the inner retina (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…4-5). This finding, while not unprecedented (de Bilbao et al, 2004), was surprising, as Ucp2 overexpression is neuroprotective in retinas exposed to excitotoxic factors (Barnstable et al, 2016) and the reverse genetic manipulation was expected to have the opposite effect. To determine the source of the observed neuroprotective phenotype, we monitored the mitochondrial morphology of Ucp2-deficient cells.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A recent study showed that mitochondrial uncoupling achieved by overexpression of UCP2 protected RGCs from glutamate excitotoxicity [29]. Thus, we hypothesized that MP201 may have similar neuroprotective properties that suppress RGC loss in optic neuritis and improve visual outcomes.…”
Section: Introductionmentioning
confidence: 96%